Silviculture in the United States: An Amazing Period of Change over the Past 30 Years. Issue 1 (25th May 2017) - D'Amato, Anthony W; Jokela, Eric J; O'Hara, Kevin L; Long, James N
Abstract: The practice of silviculture is continually evolving in response to a multitude of social, economic, and ecological factors. In 1986, the Journal of Forestry published a series of papers that reflected on changes in silviculture in the United States from the 1950s to 1980s and predicted how silviculture might develop in the next 30 years. We revisit the fundamental changes influencing the practice of silviculture since 1986; we explore how contemporary silviculture may evolve in the coming years in response to changing ownership structures on industry lands, declining research investments, and an increasing suite of stressors affecting forests, including invasive species and climate change. Many of the changes in management context and forest conditions occurring over the last 30 years were not anticipated and have resulted in an increase in silvicultural systems that integrate ecological and noneconomic social values on public lands. Many advances reflect a legacy of investment in silvicultural research and development in the 1970s and 1980s.